Investigation of Sheet Thickness and Punch Force in Die Surface Angled Hydro-mechanical Deep Drawing Method - Ballikaya, Hasan; Savaş, Vedat; Özay, Çetin (TUBITAK, 2023)
In this study, the effect of die surface angled hydro-mechanical deep drawing method on sheet metal cup wall thickness and punch force was investigated as experimental and numerical analysis. In the works, 0.9 mm thick DIN EN 10130-1999 sheet metal material was used. The effect of variables on the test results was investigated by using die surface/blank holder angle, punch nose radius, die shoulder radius, chamber pressure and blank holder force as experimental parameters. Numerical analysis experiments were carried out using ANSYS 15.0 package program. Besides, experiments were performed according to the Taguchi experi ment plan and L18 orthogonal array. The obtained data were analysed statistically by ANOVA analysis of variance in MINITAB 17.0 package program, and the effect of each parameter on the results was determined as a percentage. As a result, it was determined that the thinning was approximately 15% at most and the thickening was 10%. © 2023, TUBITAK. All rights reserved.
Keywords: Cup wall thickness; Die surface angled hydro-mechanical deep drawing; FEM; Punch force; Taguchi